Study on High Performance Surveillance and Operating Robot with Raspberry Pi - Vaishali Sharma; Simranpreet Kaur; Ritika Mahajan; Shubham Chawla; Tarush Khatri; Minal Dhankar (New Approaches in Engineering Research Vol. 13, 2021)
In this chapter, we are using the Raspberry Pi’s features to create a robot vehicle that is entirely controlled by the Raspberry Pi. Every month, a new technology is introduced in some part of the world; this statement allows us to evaluate how quickly the world is evolving in the field of science and technology. . Our main purpose of studying raspberry pi was to explore ourselves in the field of IOTs (Internet of Things). If we look at the current technological era, we can see that nanotechnology, robotics, artificial intelligence, the internet of things, and automation are all on the horizon.One of the things we’re looking into is the development of small CPUs, or the Raspberry Pi. The Raspberry Pi is based on the ARM architecture.